Application of AI-based Flipped Classroom Method in Improving English Speaking Skills - Ratna Ayu Pawestri Kusuma Dewi; Roya Zahir; Satrio Binusa Suryadi (Yayasan Adra Karima Hubbi, 2025)
Background. Speaking is a crucial component of English language acquisition, yet it remains one of the most challenging skills to master among EFL learners. Traditional teaching methods often fail to provide sufficient opportunities for oral practice and personalized feedback. Purpose. This study aims to examine the application of an AI-based flipped classroom method and its impact on improving English speaking skills, particularly in the areas of fluency, pronunciation, coherence, and accuracy among senior high school students. Method. A quasi-experimental design was employed involving 60 students divided into control and experimental groups. The experimental group was taught using AI-integrated flipped learning, incorporating tools such as speech recognition and automated feedback systems. Results. Findings indicate that the experimental group outperformed the control group in all speaking components. The most significant improvements were observed in fluency and pronunciation, attributed to regular, individualized AI-guided speaking practice. Conclusion. The AI-based flipped classroom approach offers a valuable instructional model that merges active learning with intelligent technology. It facilitates personalized, adaptive, and continuous speaking practice, thereby supporting accelerated language acquisition.